2019
DOI: 10.1136/bmjopen-2019-031692
|View full text |Cite
|
Sign up to set email alerts
|

Does diabetes influence the probability of experiencing chronic low back pain? A population-based cohort study: the Nord-Trøndelag Health Study

Abstract: ObjectiveLow back pain (LBP) is a major problem in modern society and it is important to study possible risk factors for this disorder. People with diabetes are often affected by LBP, but whether diabetes represents a risk factor for LBP has not been studied in detail. The aim of this study was to explore the association between diabetes and subsequent risk of chronic LBP.DesignAn 11-year follow-up study.SettingThe Nord-Trøndelag Health Study (HUNT2; 1995–1997) and HUNT3 (2006–2008) surveys of Nord-Trøndelag C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
3
11
0
Order By: Relevance
“…Nine of the studies (36%) used the same population data from HUNT studies. 46 , 57 63 , 97 The results that were only observed from HUNT studies were body height 60 and measures, 59 diabetes, 57 blood pressure, 46 , 62 and pulse pressure. 62 However, the risk of bias in this particular study population can be assessed as low because of the large sample size and long follow-up period.…”
Section: Discussionmentioning
confidence: 98%
“…Nine of the studies (36%) used the same population data from HUNT studies. 46 , 57 63 , 97 The results that were only observed from HUNT studies were body height 60 and measures, 59 diabetes, 57 blood pressure, 46 , 62 and pulse pressure. 62 However, the risk of bias in this particular study population can be assessed as low because of the large sample size and long follow-up period.…”
Section: Discussionmentioning
confidence: 98%
“…Pathoanatomical changes of the spine have been linked as a consequence of the hyperglycemia and altered fat metabolism commonly present in diabetes [ 25 , 26 , 27 ], and changes in health style and diet habits associated with chronic pain can lead to type 2 diabetes [ 28 , 29 ]. In fact, current literature tends to support the hypothesis that these conditions share common risk factors, such as obesity and less physical activity, instead of a causal relationship, as no causality could be determined in the longitudinal studies previously conducted [ 10 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…13 In terms of chronic physical conditions, an increasing body of research has investigated the relationship between diabetes and back pain, but there are some discrepancies in the results of these studies. [14][15][16][17][18][19][20][21] For example, a Spanish case-control study including 4190 individuals with and without diabetes revealed that CLBP and chronic neck pain were more common in people with diabetes. 20 By contrast, another cross-sectional study, using data pertaining…”
Section: Introductionmentioning
confidence: 99%